Biases in Charitable Giving to International Humanitarian Aid: The Role of Psychic Distance. (December 2018) - Mittelman, Robert; Dow, Douglas
At a time when government support for international humanitarian aid is decreasing, organizations devoted to helping in times of disaster are looking ever more to the individual donor for financial contributions. In this paper, we explore the relationship between the donor and the distant other by introducing the concepts of psychic distance and psychic distance stimuli to the macromarketing literature and exploring the role of psychic distance in fundraising for international humanitarian aid. It is our contention that by better understanding the biases that psychic distance introduce into the system, an improved flow of donations for the betterment of the distant needy and a more effective marketing system can be achieved. We offer four propositions for future testing and exploration.